A Confirmation of Indonesian EFL Students' Achievement and Views in Translation through Mobile-Assisted Language Learning - Danti Pudjiati; Sianna; Tira Nur Fitria (Al-Lisan: Jurnal Bahasa, 2022)
MALL in translation is increasingly prevalent among Indonesian EFL students due to ICT development and practical usage in teaching and learning. In addressing this issue, this research assessed the students' success and understanding by using MALL to translate a coronavirus text. There are four issues to consider: 1) Is MALL helpful in improving students' translation abilities? 2) How do students see MALL translate a text from English to Indonesian? 3) How does MALL help them cope with language competency when translating a text from English to Indonesian? 4) What challenges do students have while translating a text from English to Indonesian using MALL? This research was performed using qualitative and quantitative methods (Mix Methods). The research possessed 85 undergraduate students from East Jakarta and South Sulawesi as the respondents. Data was amassed through an online survey, a semi-structured interview, and document analysis. After attending the MALL online learning session, a paired-sample t-test indicated a significantly different score across the students. According to the survey, interview, and document analysis findings, they had a positive attitude about MALL for translation. They had acquired powerful support in terms of word order, word choice, and sentence structure. Nonetheless, most of them agreed that the technical issue and the lack of assistance were the most significant obstacles to successfully operating the MALL for translation.